2020
DOI: 10.4293/jsls.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Upper Gastrointestinal Pathology in Patients with Obesity on Preoperative Endoscopy

Abstract: Background and Objectives: The preoperative work up for bariatric surgery is variable and not all centers perform a preoperative upper gastrointestinal endoscopy. A study was undertaken to determine the frequency of clinically significant gross endoscopic and pathological diagnoses in a large sample of patients with obesity undergoing work-up for bariatric surgery. Methods: Routine endoscopy was performed on all preoperative bariatric patients. A retrospective chart review of 1000 consecutive patients was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The most common endoscopic pathology documented in this study was gastritis, found in 88 (80%) patients from either group; this observation is consistent with the results of previous studies [36]. Gastric polyps are often benign lesions, but may also be precursors for precancerous conditions and gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common endoscopic pathology documented in this study was gastritis, found in 88 (80%) patients from either group; this observation is consistent with the results of previous studies [36]. Gastric polyps are often benign lesions, but may also be precursors for precancerous conditions and gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of these pathologies did not differ significantly between the group with obesity and normal body weight. However, according to some authors [36], gastritis found during preoperative EGD may correlate with postoperative anastomotic ulceration. This implies that preoperative diagnosis and treatment of gastritis might contribute to better outcomes of bariatric treatment [37,38].…”
Section: Discussionmentioning
confidence: 95%
“…[ 13 ] In a study done by Makiewicz et al . [ 14 ] UGIE showed hiatus hernia (23.5%), oesophagitis (9.5%), H. Pylori infection (7.1%), gastric erosions (5.7%), and duodenitis (3.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BE in the literature varies between 0.2 and 3,1% and reached 7,89% in GERD population [ 30 , 31 ]; GERD incidence ranges from 10 to 20% in the general population. In our study, the rate of BE was 0.3%, and that of GERD was 9.6%.…”
Section: Discussionmentioning
confidence: 99%